Relating thermodynamic quantities of convex-hard-body fluids to the body's shape - Thomas Franosch; Cristiano De Michele; Rolf Schilling (Physical Review Research)
For a fluid of convex hard particles, characterized by a length scale σ_{min} and an anisotropy parameter ε, we develop a formalism allowing one to relate thermodynamic quantities to the body's shape. In a first step, its thermodynamics is reduced to that of spherical particles. The latter have a hard core of diameter σ_{min} and a soft shell with a thickness εσ_{min}/2. Besides their hard core repulsion at σ_{min}, they interact by effective entropic forces which will be calculated. Based on this mapping, a second step provides a perturbative method for the systematic calculation of thermodynamic quantities with the shape anisotropy ε as a smallness parameter. In leading order in ε, the equation of state is derived as a functional of the particle's shape. To illustrate these findings, they are applied to a one- and two-dimensional fluid of ellipses and compared with results from different analytical approaches and our computer simulations. The mapping to spherical particles also implies that any phase transition of spherical particles, e.g., the liquid-hexatic transition, also exists for the nonspherical ones, and shifts linearly with ε for weak shape anisotropy. This is supported by our Monte Carlo simulation.